State of the art of data mining of tree structured information - Tan, H.; Hadzic, Fedja; Dillon, Tharam S.; Chang, Elizabeth (CRL Publishing, 2008)
This paper presents the current state-of-the-art of the existing work in the area of tree mining with association rule mining as the case in point and XML mining as one applicable example. We discuss the increasing adoption of XML as a data exchange and storage medium and the challenges it poses in the area of frequent pattern mining. The main focus is on the elements of association mining, problems of tree enumeration, candidate generation and frequency counting.